2013
DOI: 10.1177/0192623313478206
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Progressive Glomerulonephropathy in Common Marmosets (Callithrix jacchus)

Abstract: Spontaneous progressive glomerulonephropathy often occurs in common marmosets. However, there are few detailed reports concerning the agerelated progressive process of glomerular changes. We discuss the glomerular changes in the early stage and the progressive changes in the advanced stage of nephropathy. We investigated the kidneys of common marmosets (2-11 years old; 9 males and 12 females) using hematoxylin and eosin, periodic acid-Schiff, periodic acid-methenamine-silver, and Masson's trichrome (MT) stains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Further, renal lesions were the most common lesion and of increased severity in the aged cohort. Histopathologic features were consistent with previously described renal pathologies in the common marmoset (Collins et al, 2014;Isobe et al, 2012;Tardif et al, 2011;Yamada, Sato, Kanno, Wako, & Tsuchitani, 2013) While we found no significant differences between young and old marmosets in the percent of time they were active versus at rest during daily behavioral observations, we did find that the way they moved within the cage differed. Older marmosets were significantly less likely to transition between quadrants within the cage than were young animals, suggesting that while they are moving they are not covering the same distances within the cage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, renal lesions were the most common lesion and of increased severity in the aged cohort. Histopathologic features were consistent with previously described renal pathologies in the common marmoset (Collins et al, 2014;Isobe et al, 2012;Tardif et al, 2011;Yamada, Sato, Kanno, Wako, & Tsuchitani, 2013) While we found no significant differences between young and old marmosets in the percent of time they were active versus at rest during daily behavioral observations, we did find that the way they moved within the cage differed. Older marmosets were significantly less likely to transition between quadrants within the cage than were young animals, suggesting that while they are moving they are not covering the same distances within the cage.…”
Section: Discussionsupporting
confidence: 90%
“…Gross and histopathologic findings were consistent with previous surveys of background and pathologic lesions in captive and wild common marmosets (Bleyer et al, 2017;Chalmers, Murgatroyd, & Wadsworth, 1983;Chamanza, 2011;Chamanza et al, 2006;David et al, 2009;Foster, 2005;Kaspareit, Friderichs-Gromoll, Buse, & Habermann, 2006;Ludlage & Mansfield, 2003;Okazaki et al, 1996;Ross et al, 2012;Tardif et al, 2011;Tucker, 1984). Few reports have focused on further defining age-associated diseases in the common marmoset (Isobe et al, 2012;Ross et al, 2012;Tardif et al, 2011;Yamada et al, 2013). All of the geriatric animals were found to have multiple abnormal histopathologic findings across multiple organ systems, while only some of the younger animals had multiple histopathologies (Table 1 and Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…Many of the incidental changes in Old World macaques discussed above, such as mononuclear cell infiltrates of various organs, chronic colitis, myocarditis, cardiomyopathy, vasculocentric inflammation, amyloidosis, glomerulonephritis/glomerulonephropathy, and lymphoid hyperplasia, can also be observed in marmosets [19,25,35,36]. Mononuclear cell infiltrates are most commonly observed in the kidneys (79%), liver (36%), adrenals (28%), thyroid (25%), heart (14%), lung (13%), and sciatic nerve (9%) [35].…”
Section: Marmosets (C Jacchus)mentioning
confidence: 99%
“…Spontaneous progressive nephropathy dominated by glomerular lesions in common marmosets has been reported 20 , 21 . The historical renal lesion in common marmosets is characterized by glomerular lesions with an increase in mesangial matrix, which progresses with aging, and secondary tubulointerstitial lesions, including tubular hyperplasia 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The marmoset has been used successfully by a number of pharmaceutical and biotechnology companies to support clinical trials and for product registration with the United States (US) Food and Drug Administration (FDA) and the European Medicines Agency (EMA) 14 , 15 . In addition, the common marmoset shows a higher incidence of renal lesions including glomerulo- and tubulointerstitial nephritis or progressive nephropathy 16 , 17 , 18 , 19 , 20 , 21 compared with that in the cynomolgus monkey 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%